Application of Cubic Nonlinear Regression on the Effects of Rainfall on Rice Harvest Results - Retno Tri Vulandari; Bebas Widada; Teguh Susyanto; Dhian Dwi Hermawan (International Journal of Trends in Mathematics Education Research, 2020)
Sukoharjo rice yields fluctuate every year. There is no system used for predicting rice yields in the Sukoharjo region, this results in a lack of information to increase rice production in Sukoharjo Regency.The purpose of this study is to apply the Cubic Nonlinear regression method to predict rice yields in Sukoharjo Regency, taking into account the influence of average rainfall on the prediction of rice yields.The design method uses Unified Model Language (UML), the application is designed with the vb net programming language and sql server database system, testing the functionality using the Black Box Test and testing the validity using MAPE. The calculated data is the 2016 data. The results of the study show predictions in 2017 have a MAPE of . This shows the prediction error rate of Based on the results of the functionality test, 100% of the applications function.